2003
DOI: 10.1160/th03-02-0105
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced TNFα and oxidative stress in patients with heart failure: effect of TNFα on platelet O2 - production

Abstract: Experimental studies have suggested that TNF alpha, a pro-inflammatory cytokine, may contribute to the deterioration of cardiovascular function through various mechanisms, including the generation of reactive oxygen species. It has not yet been demonstrated whether TNF alpha has prooxidant activity in patients with heart failure, and what the mechanism eventually resulting in this effect are. We analyzed 42 patients (38 men and 4 women, aged 26 to 74 years) with heart failure, secondary to idiopathic dilated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 48 publications
(60 reference statements)
1
21
0
1
Order By: Relevance
“…Experimental studies have suggested that TNFa contributes to the generation of ROS [6,23] with a mechanism that could involve the activation of NADPH oxidase [6,7]; however, direct evidence in support of this hypothesis is still lacking. Herein we provide the first evidence that TNFa elicits the activation of NADPH oxidase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies have suggested that TNFa contributes to the generation of ROS [6,23] with a mechanism that could involve the activation of NADPH oxidase [6,7]; however, direct evidence in support of this hypothesis is still lacking. Herein we provide the first evidence that TNFa elicits the activation of NADPH oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanisms have not been fully elucidated. TNFa-induced oxidative stress may have a role as oxidative stress is also implicated in HF deterioration [6,7]. So far, however, the mechanism linking TNFa with oxidative stress is undefined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatments available for myocardial infarction (MI) like ischemic injury targets restoration of blood supply to ischemic tissue and prevent the damage inflicted at the time of injury. While at one hand, imbalance between myocardial blood supply and demand resulting in development of ischemia and induction of necrosis in myocardium results in acute MI [3], oxidative stress produced by generation of free radicals or reactive oxygen species also plays a key role in MI development [4], [5]. Therefore, suppressing free radical generation and/or augmentation of endogenous antioxidant enzymes is reported to limit the infarct size and attenuate myocardial dysfunction [6].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of ROS-like hydroxyl radicals and superoxide anions during heart ischemia lead to destruction of the cell membrane, development of lipid peroxides, and damage to the antioxidative defense system [2,3]. Experimental and clinical studies have shown that the infarct size of myocardial necrosis may be limited by the development of endogenous antioxidant enzymes and the suppression of free radical generation [4].…”
Section: Introductionmentioning
confidence: 99%